Sleep Physiology and Dreams Subjective Meaning - Nesterenko, I. (Vìsnik (Kiïvsʹkij ìnstitut bìznesu ta tehnologìj), 2019)
Earlier, scientists believed that sleep is necessary for the "rest" of brain neurons, and therefore sleep should be characterized by a decrease in the activity of brain neurons during this period. However, studies of the electrical activity of individual brain neurons during sleep have shown that during sleep, overall, there is no decrease in the average frequency of neuronal activity compared to the state of restful wakefulness. Currently, sleep research and diagnosis of its pathologies are performed using polysomnography, a system of recording brain activity (EEG), eye movements, muscle activity or skeletal muscle activation (EMG), and heart rate (ECG). During sleep, the metabolic processes in the cerebral cortex do not fall (slow sleep phase); as one would expect, but instead they grow (in the fast-sleep phase), resulting in the sleeping person's brain consuming more oxygen than the human being in a state of alertness. In general, a person's dream has a proper cyclic organization. Electroencephalographic analysis of night sleep allows distinguishing five stages. The first four refer to the slow phase of sleep, the fifth to the fast. The peculiarity of the interpretation of dreams is the first science known by Z. Freud. His theory has a reverse temporal direction toward childhood experiences and childhood suppressed desires. In the Jungian approach, the overall function of dreams is to try to restore our mental balance through the production of dream material, which restores - in a very delicate way - a wholesome mental balance. In the framework of Gestalt Therapy by F. Perls he believed that in order to understand the meaning of dreams, it was better not to interpret it. Given that dreaming is a projection where all the actors and objects that appear in it are the dreamer, it is more appropriate to find feelings about the objects and subjects of sleep. Therefore, it can be argued that the human brain is active during sleep, although this activity is qualitatively different than during the state, and in different stages of sleep has its specificity. Since the formation and development of Freud's views, dreams have been recognized by psychotherapists as an essential key on the path from unconscious material to the achievement of human integrity.